Evidence that a higher ATP cost of muscular contraction contributes to the lower mechanical efficiency associated with COPD: Preliminary findings - Layec, G.; Haseler, Luke; Hoff, J.; Richardson, R. (2011)
Impaired metabolism in peripheral skeletal muscles potentially contributes to exercise intolerance in chronic obstructive pulmonary disease (COPD). We used 31 P-magnetic resonance spectroscopy ( 31 P-MRS) to examine the energy cost and skeletal muscle energetics in six patients with COPD during dynamic plantar flexion exercise compared with six well-matched healthy control subjects. Patients with COPD displayed a higher energy cost of muscle contraction compared with the controls (control: 6.1 ± 3.1% of rest·min -1 ·W -1 , COPD: 13.6 ± 8.3% of rest·min -1 ·W -1 , P = 0.01). Although, the initial phosphocreatine resynthesis rate was also significantly attenuated in patients with COPD compared with controls (control: 74 ± 17% of rest/min, COPD: 52 ± 13% of rest/min, P = 0.04), when scaled to power output, oxidative ATP synthesis was similar between groups (6.5 ± 2.3% of rest·min -1 ·W -1 in control and 7.8 ± 3.9% of rest·min -1 ·W -1 in COPD, P = 0.52). Therefore, our results reveal, for the first time that in a small subset of patients with COPD a higher ATP cost of muscle contraction may substantially contribute to the lower mechanical efficiency previously reported in this population. In addition, it appears that some patients with COPD have preserved mitochondrial function and normal energy supply in lower limb skeletal muscle. © 2011 by the American Physiological Society.